2017
DOI: 10.3390/met7100439
|View full text |Cite
|
Sign up to set email alerts
|

Application of Co and Mn for a Co-Mn-Br or Co-Mn-C2H3O2 Petroleum Liquid Catalyst from the Cathode Material of Spent Lithium Ion Batteries by a Hydrometallurgical Route

Abstract: Abstract:We investigated the preparation of CMB (cobalt-manganese-bromide) and CMA (cobaltmanganese-acetate) liquid catalysts as petroleum liquid catalysts by simultaneously recovering Co and Mn from spent Li-ion battery cathode material. To prepare the liquid catalysts, the total preparation process for the liquid catalysts consisted of physical pre-treatments, such as grinding and sieving, and chemical processes, such as leaching, solvent extraction, and stripping. In the physical pre-treatment process, over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…The chemical composition of the LIB cathode materials was analyzed by ICP-OES and mainly contained 25.83% Co, 26.29% Ni, 14.41% Mn, and 8.31% Li. Compared with previous literature [41], we found that the total amount of Co and Ni in this study was nearly 15% higher than in previous literature. Because of the similar chemical properties of Co and Ni, a large proportion of Co and Ni causes serious co-precipitation and co-extraction, as well as other negative effects.…”
Section: Materials and Reagentscontrasting
confidence: 89%
“…The chemical composition of the LIB cathode materials was analyzed by ICP-OES and mainly contained 25.83% Co, 26.29% Ni, 14.41% Mn, and 8.31% Li. Compared with previous literature [41], we found that the total amount of Co and Ni in this study was nearly 15% higher than in previous literature. Because of the similar chemical properties of Co and Ni, a large proportion of Co and Ni causes serious co-precipitation and co-extraction, as well as other negative effects.…”
Section: Materials and Reagentscontrasting
confidence: 89%
“…[6,17,18] have been extensively investigated. Metals and metal oxides are common catalysts [19][20][21][22][23][24]. APPs also have been used for syntheses and post-treatments of catalysts [25].…”
Section: Preparation Of Pt-sno X Cesmentioning
confidence: 99%
“…The preparation of petroleum liquid catalyst [11], Sn-incorporated LiNi x Co y Mn z (NCM) [12], Ni nanosized powder [13] was investigated using leach liquor of a lithium ion battery (LIB). Joo et al [11] introduced a comprehensive recycling process, which included physical separation, leaching, solvent extraction and stripping, to prepare CMB (cobalt-manganese-bromide) and CMA (cobalt-manganese-acetate) liquid catalysts as petroleum liquid catalysts from the cathode materials of spent lithium ion batteries.…”
Section: Preparation Of Valuable Materials From Wastementioning
confidence: 99%
“…The preparation of petroleum liquid catalyst [11], Sn-incorporated LiNi x Co y Mn z (NCM) [12], Ni nanosized powder [13] was investigated using leach liquor of a lithium ion battery (LIB). Joo et al [11] introduced a comprehensive recycling process, which included physical separation, leaching, solvent extraction and stripping, to prepare CMB (cobalt-manganese-bromide) and CMA (cobalt-manganese-acetate) liquid catalysts as petroleum liquid catalysts from the cathode materials of spent lithium ion batteries. Kang et al [12] investigated the effect of Sn impurity on the LIB performance of Ni-rich NCM, resynthesized from leach liquor of spent LIB by conducting analyses such as scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) mapping, X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS).…”
Section: Preparation Of Valuable Materials From Wastementioning
confidence: 99%